Features of formation of psychological structure of children's and teen's aggression - A B Kruchkova (Peoples' Friendship University of Russia (RUDN University), 2009)
The research paper analyzes the factors influencing the aggressive behaviour formation system at teenagers of 14-15 years, as well as cites data finding-out prevailing forms of aggressive behaviour peculiar to the given age category.